Human Resource Staff Perceptions of Training Functions as Practised in Selected Hotels in Penang - Abdul Jalil, Azlita (2002)
Training functions are widely needed and known for it' s importance in organisations all over the world. Top management needs to be committed .to training functions and development activities. This is because top management plays critical role in the success or failure of any training functions. Unfortunately, in Malaysia, it is not given sufficient focus yet as it is assumed to be costly and a waste of time, but in hotel industry, training is needed very much as it involves the staff skills and performance. This study examined the background characteristics of selected hotels in Penang, the contributing factors of the improper practice of training functions in hotels. This is a descriptive survey research. It utilised questionnaires as the mode of data collection. The data was analysed in descriptive statistics. The nature of the population and questions to be answered in this study warranted the use of quantitative research approach. The respondents of the research were the staff of human resource departments of the selected hotels in Penang. Questionnaires were distributed and collected personally from 44 respondents of 15 selected hotels in Penang. From the research, it was found that the training functions practised differs between small, medium and big organisations. Bigger hotels have a well sorted plan for training functions and the improper practice of training functions in big hotels are not big compared to smaller hotels. This is seen from the capability of the hotel's finances, manpower and expertise in HR Departments to carry out training functions. The contributing factors to the improper practice of training functions in hotels are due to five contributing factors which is the lack of the realization of training functions, lack of manpower in HR departments, lack of financial requirement to run training functions, lack of management's policy, leadership, skills, knowledge, attitudes and expertise to operate training functions and the lack of realization of the outcome of training functions in hotels. Results show that the factors do influence training functions practised in hotels. This study can be a guide for the hotels for improvement in their training functions with the realisation of the improper practice of training functions in their organisations.